OPTIMIZATION OF NEUROTRANSMITTERS SEPARATION UNDER HILIC CONDITIONS - RALUCA TAMPU (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2017)
This paper presents the optimization of a hydrophilic interaction chromatographic method for the separation of eleven catecholamines, indolamines and their precursors and metabolites. The studied parameters are: the organic modifier nature and percentage, the salt nature and concentration, the mobile phase pH and the column temperature. The best results in terms of separation were obtained using a mobile phase composed of acetonitrile and ammonium formate (150 mM pH 3) 85:15 v:v.